Heavily Indebted Poor Countries (HIPC) Initiative and Multilateral Debt Relief Initiative (MDRI) : Statistical Update. (Policy Papers; Policy Paper ;, 2017)
The HIPC Initiative and MDRI are nearly complete, with 36 countries having reached the completion point under the HIPC Initiative. Debt relief under the Initiative has alleviated debt burdens substantially in recipient countries and has enabled them to increase their poverty-reducing expenditure by over one and a half percentage points of GDP between 2001 and 2015. Creditor participation in the HIPC Initiative has been strong amongst the multilateral and Paris Club creditors; however participation from other creditor groups still needs to be strengthened. The total cost of debt relief to creditors under the HIPC Initiative is currently estimated to be USD 76.9 billion, while the costs to the four multilateral creditors providing relief under the MDRI is estimated at USD 42.4 billion in end-2015 present value terms.